Post-traumatic stress disorder among Al-Quds University students during the 2023 Gaza war: a cross-sectional study - Akram Amro; Alhareth M. Amro; Raghda Amro; Mahmoud Hamdan (BMC Psychiatry)
Abstract Background The 2023 Gaza War has had profound psychological impacts on Palestinian students, particularly those at Al-Quds University. Students at Al-Quds University face significant mental health challenges due to exposure to conflict-related trauma, which is exacerbated by direct and indirect stressors, including displacement and the influence of social media. This study aims to assess the prevalence of PTSD among Al-Quds University students and investigate its associations with demographic, psychological, and academic factors, specifically gender, living arrangements, academic specialization, and geographic origin. Methodology This descriptive cross-sectional study assessed PTSD prevalence among students at Al-Quds University using the Impact of Event Scale-Revised (IES-R), a validated tool for PTSD assessment in this context. A bilingual (Arabic and English) self-administered questionnaire was distributed online. Statistical analyses, including chi-square tests, independent t-tests, and ANOVA, were conducted using SPSS version 20.0 to examine associations between PTSD symptoms and demographic or psychological factors. Results High PTSD symptom severity was reported in 71.3% of participants, with 14.7% identified as probable cases and 10.7% with clinical concerns. Gender differences were evident, as males showed higher mean PTSD scores than females (49.39 vs. 43.22, p < 0.001). Students in student housing exhibited significantly higher PTSD scores than those living with family (49.37 vs. 42.16, p < 0.001). Psychological factors, such as perceived academic disruption and guilt during positive events, were significantly associated with PTSD severity (p = 0.037, p = 0.005). Conclusion The findings emphasize the urgent need for trauma-informed mental health interventions tailored to students in conflict zones. Addressing systemic stressors and providing targeted support can mitigate the psychological burden in these vulnerable populations. Clinical trial number Not applicable.